The psychological health and well-being of emergency medicine consultants in the UK. Issue 7 (13th October 2016) - Fitzgerald, Katherine; Yates, Philip; Benger, Jonathan; Harris, Adrian
Abstract : Objective: To explore the experience of psychological distress and well-being in emergency medicine (EM) consultants. Methods: A qualitative, interpretative phenomenological analysis (IPA) study based on 1:1 semistructured interviews with EM consultants working full time in EDs across South West England. Eighteen EM consultants were interviewed across five EDs, the mean (SD) age of participants being 43.17 (5.8) years. The personal meanings that participants attached to their experiences were inductively analysed. Results: The analysis formed three superordinate themes: systemic pressures, physical and mental strain and managing the challenges. Pressures within the ED and healthcare system contributed to participants feeling undervalued and unsatisfied when working in an increasingly uncontrollable environment. Participants described working intensely to meet systemic demands, which inadvertently contributed to a diminishing sense of achievement and self-worth. Consultants perceived their experience of physical and emotional strain as unsustainable, as it negatively impacted; functioning at work, relationships, personal well-being and the EM profession. Participants described how sustainability as an EM consultant could be promoted by social support from consultant colleagues and the ED team, and the opportunity to develop new roles and support ED problem solving at an organisational level. These processes supported a stigma-reducing means of promoting psychological well-being. Conclusions: EM consultants experience considerable physical and mental strain. This strain is dynamically related to consultants' experiences of diminishing self-worth and satisfaction, alongside current sociopolitical demands on EM services. Recognising the psychological experiences and needs of EM consultants and promoting a sustainable EM consultant role could benefit individual psychological well-being and the delivery of emergency care.